PERSEPSI AUDIENS PADA PEMBERITAAN CITIZEN JOURNLISM AKUN INSTAGRAM @prfm - Chidayah, Prita Priantini Nur; Widianti, Nur Ai’ni (Annaba: Jurnal Ilmu Jurnalistik, 2024)
This research aims to find out the selection process, interpretation process, and audience reactions to citizen journalism news on @prfm Instagram account. The research uses a qualitative descriptive study method that describes the research results in detail regarding audience perceptions. The theory taken is the theory of the perception process from Soelaeman in Sobur (2003). Data sources were taken from interviews with five informants who are followers of @prfmnews Instagram. The audience selection process involves attention to personal factors and situational factors of human behavior and. The interpretation process occurs involving traffic news as the most remembered news in the news due to the interest in the latest information and relying on the reliability of the communicator's credibility. The positive reaction process has a beneficial impact on all audiences from various layers, especially in the impression process of causality attribution which is the result of focusing on behavior.